Effects of distribution, behavior, and climate on mule deer survival. Issue 1 (26th August 2018) - Schuyler, Elizabeth M.; Dugger, Katie M.; Jackson, Dewaine H.
ABSTRACT: Mule deer ( Odocoileus hemionus hemionus ) populations in North America are a valuable economic wildlife resource, with the managed harvest of this species reflecting societal values and recreational opportunities in many parts of the western United States. Managing mule deer populations while allowing for harvest requires an understanding of the species' population dynamics, including the specific factors associated with population change. We conducted a 7‐year (2005–2012) study designed to investigate habitat use and survival of mule deer in eastern Oregon, USA. We used known‐fate data for 408 adult female radio‐collared mule deer to estimate monthly survival rates and to investigate factors that might affect these rates, including seasonal distribution, temporal effects (seasonal, annual, and trends across season and year), movement behavior, and local weather and regional climatic covariates. Variation in survival rates of female mule deer was best explained by an additive effect of migration behavior, differences in survival during the fall migration period compared to the rest of the annual cycle, and precipitation levels on winter ranges of individual deer. Estimates of annual survival were higher for migrants (0.81–0.82), compared to residents (0.76–0.77). Survival was lower for migrants and residents during fall migration (Oct–Nov) and higher amounts of winter precipitation increased survival of both groups. The results of our study suggest that migrating to potentially higher quality summer foraging areas outweighed the cost of traveling through unfamiliar habitats and energy expenditure associated with migration. © 2018 The Wildlife Society. Abstract : Higher monthly survival rates of mule deer migrants compared to residents suggested that leaving for potentially higher quality summer foraging grounds outweighed the cost of traveling through unfamiliar habitats and energy expenditure from migration. Migrants and residents had lower monthly survival during the fall migration period (Oct–Nov) and winter precipitation had a positive effect on survival for both groups, possibly because increased average winter precipitation resulted in increased winter forage quantity and quality.